The relationship between knowledge management and organizational learning among public librarians: A case study of public librarians in Fars province - Ahmad Shabani; Hmid Pirayesh; Saeed Rajaeepour; Mariam Keshvari (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2022)
Purpose: The purpose of this study is to investigate the relationship between knowledge management and organizational learning among public librarians in Fars province. Method: This study is an applied study which was conducted using the descriptive-correlational method. The statistical population included all librarians of public libraries in Fars province in 1400 (322 people), from whom 175 librarians were selected as the research sample using simple random sampling. In order to collect people's opinions, Bukowitz and Williams (1999) standard knowledge management questionnaire and organizational learning questionnaire based on Neefe theory (2001) were used. In order to analyze the data, SPSS software version 22. and descriptive statistical methods such as frequency, percentage, mean, standard deviation, and in inferential statistics, Pearson correlation test and multiple linear regression were used. Findings: The results of correlation coefficient showed that there was a significant relationship between knowledge management (KM) and organizational learning (OL) among the librarians of public libraries in Fars province. Furthermore, among KM’s components, knowledge production and consolidation and sharing had the most correlation with OL (respectively 0.900 and 0/898 correlation coefficients). Moreover, the result of multiple linear regression showed that there is a 100-percent common variance between KM and OL. The production and consolidation component is the strongest predictor for OL (Beta=0.197). This research showed that knowledge production and consolidation component (acquisition of required skills in accordance with organizational goals) and knowledge sharing (transfer and sharing of effective individual and organizational experiences) have the greatest relationship and impact on the promotion and improvement of OL. Originality/value: The issue of knowledge management has been an issue of concern in public library literature in recent years. However, the relationship between knowledge management and organizational learning has not been studied much; In addition, examining this issue among the community of public library librarians of Fars province has been the focus of attention in the present study. The results of this research can pave the way for library managers to try to improve knowledge and knowledge management that has led to organizational learning by planning, appropriate policies, and providing standards.